EFFECT OF GREEN HUMAN RESOURCE MANAGEMENT PRACTICES ON SUSTAINABILITY OF FOOD AND BEVERAGE COMPANIES IN NIGERIA - Richard, Agwa Terwase; Umogbai, Monica Esiebugie; Kwahar, Nguwatsen; Hanmaikyur, Tyoapine Joseph (The journal of contemporary issues in business and government, 2024)
The study examined the effect of green human resource management practices on sustainability of quoted food and beverage companies in Nigeria. The study specifically determined the effect of green recruitment, green training, green rewards, green performance appraisal, and green employee involvement on sustainability of food and beverages companies in Nigeria. The study adopted a survey research design. The population of the study included three hundred and twenty-five (325) staff of fourteen (14) quoted food and beverages companies and a census sampling approach was used to consider the entire population. Primary data collected through self-administered questionnaire were analysed using descriptive statistics and multiple regression with the aid of the Statistical Package for Social Sciences (SPSS version 25). The study found a significant positive effect of green recruitment, green training, green rewards, green performance appraisal, and green employee’s involvement on sustainability of food and beverages companies in Nigeria. The study concluded that, green human resource management practices have significantly enhanced the sustainability of food and beverages companies in Nigeria. The study recommended amongst others that, food and beverages companies in Nigeria should pay a serious attention in sustainable implementation of green recruitment practices which involves attracting and selecting candidates who are not only qualified but also have a strong commitment to green environmental practices. This practice ensures that the workforce is aligned with the company's green objectives from the onset.